"The Indians Stationary Here": Continuity and Change in the Origins of the Fort Simpson Tsimshian - Patterson, E Palmer (Anthropologica, 2022)
In 1834, the Hudson's Bay Company moved its post, Fort Simpson, to a new site on the Tsimshian peninsula. This essay explores the origins, founding and first decade of the Coast Tsimshian village which formed at the new Fort Simpson. Working primarily from fort records, complemented by oral traditions, a close view is available of a variety of elements, persons and events in the village's first years. These include trading relationships involving different Tsimshian groups, Nisga'a, Tongass, Americans, Russians and others, as well as political rivalries and ceremonials. There is a record of the devastation caused by smallpox. Although the journal inevitably reflects the prejudices of the European traders, it nonetheless provides a valuable picture of the cultures of the Northwest Coast, incidentally revealing the ways in which the Tsimshian utilized the European presence.